(untitled) (Fiep Bulletin - online, 2014)
Abstract: This work explored individual and collective experience of social space through physical activities based on capoeira, and its relationship with subjective social well-being. This research was developed in Warsaw, capital of Poland. The elements of subjective social well-being were understood as believes, values, hopes and expectances (Heidegger, 2000). The interaction through connectivity was defined as the main element of social well-being (Van Manen, 1990). The specific elements of capoeira, such as capoeira game, musical instruments and the group were related to the social well-being improvement. Eighty individuals participated in this study. From that participation, fifty non-structured interviews were applied in a randomized sample during a period of 3 to 5 months of regular participation in capoeira lessons. Phenomenology and hermeneutics were considered as the methodological principles (Colaizzi, 1978; Creswell, 1997). The process of analyzing, interpreting and discussion identified positive effects when relating subjective social well-being with the social space of capoeira practicing.